2016
DOI: 10.1016/j.toxicon.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Bufadienolides from parotoid gland secretions of Cuban toad Peltophryne fustiger (Bufonidae): Inhibition of human kidney Na+/K+-ATPase activity

Abstract: Parotoid gland secretions of toad species are a vast reservoir of bioactive molecules with a wide range of biological properties. Herein, for the first time, it is described the isolation by preparative reversed-phase HPLC and the structure elucidation by NMR spectroscopy and/or mass spectrometry of nine major bufadienolides from parotoid gland secretions of the Cuban endemic toad Peltophryne fustiger: ψ-bufarenogin, gamabufotalin, bufarenogin, arenobufagin, 3-(N-suberoylargininyl) marinobufagin, bufotalinin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…In mammals, they are produced in the adrenal cortex through a pathway independent of cholesterol side-chain cleavage [47]. Bufadienolides regulates the Na + /K + -ATPase pump by inhibiting the cardiotonic steroid dependent-site [15,23]. In cancer cells, the Na + /K + -ATPase pump also acts as a scaffolding protein when localized in caveolae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, they are produced in the adrenal cortex through a pathway independent of cholesterol side-chain cleavage [47]. Bufadienolides regulates the Na + /K + -ATPase pump by inhibiting the cardiotonic steroid dependent-site [15,23]. In cancer cells, the Na + /K + -ATPase pump also acts as a scaffolding protein when localized in caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we wanted to evaluate the antiproliferative effect of toad venoms and their components on melanoma cells. This project was initiated because studies have indicated that these venoms act on the Na + /K + ATPase [14,15] which is overexpressed in many cancer types, including metastatic melanoma [24]. More interestingly so, a recent study indicated that bufalin, a molecular compound found in toad venom, was endogenously expressed in human serum and the concentrations were decreased in the case of hepatocellular carcinoma [25].…”
Section: Introductionmentioning
confidence: 99%
“…Cruz Jdos S et al also reported arenobufagin, as a potent Na+/K+ pump inhibitor, depressed the delayed rectifier K+ current of single guinea-pig ventricular cells in the whole-cell patch-clamp configuration[ 22 ]. Perera Córdova WH et al reported arenobufagin fully inhibited the Na, K-ATPase activity of normal human renal tissues in a concentration-dependent manner[ 23 ]. Li M et al reported arenobufagin inhibited vascular endothelial growth factor (VEGF)-mediated angiogenesis through suppression of VEGFR-2-mediated signaling cascades[ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most interesting trait seems a promising antitumor activity of bufadienolides including inhibition of cell proliferation and migration, induction of cell differentiation, inhibition of cancer angiogenesis, induction of apoptosis, disruption of the cell cycle, reversal of multi-drug resistance and enhancement of cytotoxic drug activity. One of the proposed molecular mechanisms of this anticancer activity is the inhibition of Na + /K + -ATPase [ 61 , 62 , 63 ]. However, medical use of bufadienolides is highly restricted due to their narrow therapeutic margins, short drug half-life and toxicity [ 64 ].…”
Section: Biological Significance and Potential Applications Of Smamentioning
confidence: 99%